Exopolysaccharides production by Lactobacillus fermentum under different growth conditions in coconut water medium - Permanasari, Etin Diah; Wahyudi , Priyo; Fauziah, Fuji; Robertlee, Jekson (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Exopolysaccharides (EPS) production gain a lot of attention over recent decades, because EPS can provide beneficial effects, not only on the industrial application but also on the health sector. The understanding of the optimal condition for EPS production will increase the productivity of EPS and can develop EPS with desirable properties. The factors affected EPS production are additional of sugar concentration, temperature, fermentation time, and others. The current work aimed to optimize the utilization of a byproduct leftover of coconut water on the EPS production from Lactobacillus fermentum. Methods: The EPS synthesis were analyzed under various growth conditions in coconut water such as additional of sucrose concentration and incubation times. EPS production of Lactobacillus fermentum was performed by adding 1%, 2%, and 3% of sucrose and 12, 24, 36, and 48 h of incubation periods. The obtained data were analyzed statistically using a two-ways ANOVA test. Results: The EPS production increased as the sucrose concentration and incubation time were increased. The optimal production was found to be in the media supplemented with 3% sucrose and 48 h of incubation period, which gave 12.613 g/L of EPS production. Conclusions: Media of coconut water is suitable for EPS production by Lactobacillus fermentum. Under 3% of additional sucrose concentration and 48 h of incubation time, it produced a larger number of EPS compare to other conditions.